The Influence of In-Group Membership on Trust in Health-Care Professionals in Kazakhstan - Brett J Craig PhD; Gulaiim Almatkyzy MS; Yuliya Yurashevich MA (Journal of Patient Experience, 2020)
Background: Trust in providers is key to positive health outcomes. However, perceptions of trust in health-care professionals can vary by population. Factors beyond the immediate behaviors of health-care professionals such as group association may influence perceptions of trust. Objective: To examine the possible association of in-group membership and levels of trust in health-care professionals in Kazakhstan. Method: We used an online survey including the General Trust in Physicians scale along with demographic questions and a question regarding family members as health-care professionals. Bivariate analysis was used to compare the mean differences between general levels of trust and sociodemographic characteristics. Then multivariate analysis was conducted to examine the association between having a family member who is a health-care professional and general level of trust in health-care professionals among Kazakhstani citizens. Statistical tests were 2-sided. Results: A total of 497 Kazakhstani participants completed the survey. In adjusted multivariate regression, participants with family members as health-care professionals scored significantly higher on the trust scale ( P < .001), and other factors such as language ( P < .001) and interaction term of language and education ( P < .05) were also shown to be influential in the general level of trust. Conclusion: Further examinations of how group membership influences reported trust levels in health-care professionals in Kazakhstan are warranted. Such studies would be beneficial if trust in health-care professionals is to be understood and improved in order to achieve more desirable health outcomes.